Monitoring Suhu Proses Sangrai Biji Kopi - Roza Susanti -; Zas Ressy Aidha; Fedri Tri Satrio (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
Temperature set of the coffee bean roasting to get the roasting temperature of arabica using thermocouple temperature cencor. Temperature monitoring is controlled by microcontroller. The suitable temperature set of roasting process determine the temperature of three conditions, they are light roast, medium roast, and dark roast. Roasting temperature set of the coffee bean have a goal to get the best quality of coffee bean.